Using a Messenger Bot as a Tool for Providing Written Corrective Feedback: Examining L2 Development and Learners’ Attitudes - Abdollahzadeh, Maryam; Golshan, Mohammad; Allami, Hamid (Research in English language pedagogy (Online), 2022)
The current study aimed to examine the effect of written corrective feedback (WCF) provided via a messenger bot on Iranian English as a foreign language (EFL) learners’ use of definite/indefinite articles. It also explored learners’ attitudes toward using the messenger bot, which worked as a medium for providing WCF on the TOEFL iBT speaking task II. Seventy male and female TOEFL candidates (mean age: 26, range: 18-34) chosen through convenience sampling participated in the study. Before the treatment, the participants in all groups were given a proficiency test and a speaking pre-test. Then, they were randomly assigned to one of the three groups: one received WCF on their errors in the use of articles through the bot (MB group, n=30); the second one received WCF in traditional classes (TF group, n=20); and the participants in the third group received no feedback and followed the normal course of instruction (NF group, n=20). Subsequently, all groups participated in a post-test The results of the mixed between-within subjects, ANOVA, showed that the MB group significantly outperformed the other two groups and there was not a significant difference between the TF and NF groups. The participants’ attitudes toward receiving WCF through the bot were elicited through in-depth semi-structured interviews. The transcribed interviews were then analyzed using the first two phases of the grounded theory, and two main themes of pedagogical applications and technological issues emerged. The implications stemming from the findings concerned the efficacy of using the messenger bot in providing corrective feedback.